Compressive Strength and Chloride Penetration Tests of Modified Type IP Cement Concrete with Rice Ash. (2017) - Javier, Anna Rose A.; Lopez, Neslyn E.; Juanzon, Joseph Berlin P.
Abstract: Concrete is one of the most widely used materials in the field of building construction. It is basically composed of aggregates such as gravel and sand, bind together by cement and water. One of the major problems with concrete structures is the corrosion of steel reinforcement. Supplementary Cementitious Materials (SCM) like fly ash, Ground Granulated Blast Furnace Slags (GGBFS), Silica Fume (SF), and rice ash have the characteristics and properties similar to cement. Studies also showed that rice ash can partially replace cement in the concrete mixture. The objective of this study is to conduct a comparative analysis on the compressive strength and chloride penetration depth with 10%, 20% and 30% replacement of the rice ash in the type IP cement. Colorimetric method was used to determine the chloride penetration depth by applying AgNO3 solution. The results were analyzed using Analysis of Variance (ANOVA). Results show that there are significant differences in each percentage replacement of rice ash in type IP cement. The 10% percent replacement obtained the highest compressive strength and chloride penetration resistance. The improvement of the strength of concrete with rice ash indicated that it was an effective way of improving not only the serviceability of concrete but also preventing chloride penetration that causes corrosion on steel reinforcement.